PENERAPAN MODEL PEMBELAJARAN NON-DIRECTIVE PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM SISWA KELAS X SMK ISLAM PEMALANG - Mar’atul Lutfiyah (Al Ghazali, 2019)
Non-directive learning emphasizes efforts to facilitate learning, achieve personal integration and maximize the thinking power possessed by students by providing support for the spirit of religious learning. Students are trained to think across disciplines, solve every problem according to their abilities and desires and must be accountable. Thus, students have more space for creativity and increase their enthusiasm for learning. The role of the teacher in this learning model is as a facilitator. The results obtained from the application of this non-directive learning model are 44.2% of students can follow the non-directive learning model, while 55.8% of students have not been able to follow the non-directive learning model. Although the results obtained are still relatively low, these results have shown that students in learning play an active role in building a more conducive classroom atmosphere.